MYCOLOGICAL PROFILE AND ANTIFUNGAL SENSITIVITY OF INFECTIVE KERATITIS IN A TERTIARY CARE HOSPITAL OF SOUTHERN ODISHA - Sumanta, Sahu; Sanghamitra, Padhi; Banojini, Parida; Abhishek, Padhi; Biswajit, Baral (International Journal of Clinical and Biomedical Research, 2018)
Background: Infective keratitis is the second major cause of blindness next to cataract. Mycotic keratitis is an important ophthalmologic problem especially in developing countries including India. Fungal infection involving cornea is a fatal condition which needs early diagnosis and treatment to save the patient’s eye. Though studies on mycotic keratitis have been reported from different part of India, to the best of our knowledge this study showing antifungal susceptibility is the first to be reported from Southern Odisha. Objective: The purpose of this study was to study epidemiological characteristics, predisposing factors, fungal etiology and antifungal susceptibility of common fungal isolates in infective keratitis cases. Materials and Methods: A prospective study was conducted from November 2015 to October2017 in the Department of Microbiology and Ophthalmology M.K.C.G Medical College and Hospital. Relevant information was recorded using standard proforma of keratitis cases. Corneal scrapings were collected under strict aseptic conditions and subjected to10% KOH mount, Gram stain and culture. Identification of fungal agents were done as per standard microbiological procedures. An antifungal sensitivity test was done by microbroth dilutions as per CLSI reference method. Results: Over a period of two years 149 patients of infective keratitis were evaluated. Microbiological diagnosis of mycotic keratitis was established in 39 (26.17%) cases. Filamentous fungi were isolated more often than yeasts. The most frequently encountered filamentous fungi and yeasts were Aspergillus spp. 14(35.89%) and Candida albicans 7 (17.94%) respectively. Males were more commonly affected and were mostly in the age group of 46-60 years. Ocular trauma due to vegetative matter was the most common predisposing factor. Natamycin was the most effective antifungal against filamentous fungi and amphotericin B was most effective for Candida albicans. Conclusion: Because of serious consequences of mycotic keratitis, it is very important to know the exact etiological agents and effective antifungals to save the eye of the patients. So laboratory confirmation should be undertaken and fungal infection should be ruled out before prescribing antimicrobial agents.